Thermal degradation and pyrolysis of mixtures based on poly(3-hydroxybutyrate-8%-3-hydroxyvalerate) and cellulose derivatives - Fraga, Alicia (2005)
Thermal degradation and pyrolysis behaviour of mixtures based on poly(3-hydroxybutyrate-co-8%-3-hydroxyvalerate) (P(HB-8%HV)) and cellulose derivatives has been studied. The effect of the formulation of mixtures in the thermal degradation of both co-components was evaluated. TG/DTG experiments and Py-GC–MS were used in this study. Solid–solid and gas–solid interactions between co-components were analyzed by using a simple mixture rule. Mixtures with microcrystalline cellulose (MC) resulted in an enhancement of thermal stability of both co-components due to strong hydrogen type interactions in the solid state and between gases evolved from polymer decomposition and solid MC. Crotonic acid seemed to induce a higher order in cellulose, causing disruption of some hydrogen bonds within it and promoting the formation of more stable cellulose structure. On the other hand, sisal fiber showed an unfavourable effect on polymer thermal stability. Acetic acid produced from hemicellulose thermal decomposition seemed to act as acid promoter for the random scission of ester linkages in P(HB-8%HV).